1997
DOI: 10.1038/sj.onc.1201384
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of lymphomagenesis by methylnitrosourea in mice transgenic for LMO1 is blocked by O6-alkylguanine DNA-alkyltransferase

Abstract: We evaluated induction of lymphomas by the methylating carcinogen, N-methylnitrosourea [MNU], in transgenic mice expressing both LMO1 and the DNA repair gene, MGMT, in the thymus. The goal was to determine whether environmental mutagens shorten the latency or increase the incidence of LMO1+lymphomas and whether mice transgenic for both LMO1 and MGMT, and thereby able to repair O 6 -methylguanine DNA adducts induced by MNU, would be protected. Mice heterozygous for LMO1 or MGMT were crossed and o spring treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
0
17
1
Order By: Relevance
“…In our study, although K-ras mutations were found, no correlation was present between these mutations and tumor latency in either PMS2 +/+ or PMS2 7/7 mice. This is in contrast to our recent report showing an association between K-ras mutation and shorter latency in LMO1 overexpressing mice (Allay et al, 1997). Thus, while K-ras mutations are observed in some MNU-induced lymphomas, other oncogenes and/or inactivation of unidenti®ed tumor suppressor gene(s) may also be involved, and may complement the presence of K-ras mutations.…”
contrasting
confidence: 98%
See 1 more Smart Citation
“…In our study, although K-ras mutations were found, no correlation was present between these mutations and tumor latency in either PMS2 +/+ or PMS2 7/7 mice. This is in contrast to our recent report showing an association between K-ras mutation and shorter latency in LMO1 overexpressing mice (Allay et al, 1997). Thus, while K-ras mutations are observed in some MNU-induced lymphomas, other oncogenes and/or inactivation of unidenti®ed tumor suppressor gene(s) may also be involved, and may complement the presence of K-ras mutations.…”
contrasting
confidence: 98%
“…at 5 weeks of age. High expression of hMGMT + reduced the incidence from 100% in the PMS2 7/7 mice to 80% in the PMS2 7/7 /hMGMT + mice (the thymic lymphoma-free survival rate was 0 vs 20% in PMS2 7/7 mice and PMS2 7/7 / hMGMT + mice, respectively, P50.001) and signi®cantly increased the mean latency 81 to 91 days, P50.05) lymphomas in MSH2-de®cient mice (Lowsky et al, 1997) and MNU-induced thymic lymphomas (Allay et al, 1997). Mice groups were analysed for incidence and latency of lymphoma induction.…”
mentioning
confidence: 99%
“…In practice, there is little evidence that such a chemoprotective strategy would promote leukemia in cells which overexpress MGMT. In fact, gene modified hematopoietic cells demonstrate a significant reduction in mutation frequency and chromosomal aberrations upon challenge with O 6 alkylating agents [ 31,[82][83][84] and mice transgenic for human MGMT show a decrease in cellular transformation frequency upon drug treatment [85][86][87][88][89]. Perhaps most compelling in this regard is the observation that there was no evidence of hematopoietic malignancy following an extended, dose escalating chemotherapeutic regimen in a canine large animal model which enabled selection of gene modified cells [ 62 ].…”
Section: Chemoselection and Stem Cell Biologymentioning
confidence: 98%
“…While this is still an area of active investigation, there is no evidence to date that overexpression of mutant forms of MGMT and exposure to alkylating agents can lead to leukemia. To this end, several groups have demonstrated that hematopoietic cells transduced with retroviral vectors that express MGMTmutant proteins do not show an increased in the frequency of mutations or chromosomal aberrations upon challenge with O 6 alkylating agents (Allay et al, 1997;Chinnasamy et al, 1998a;Chinnasamy et al, 1998b;Dumenco et al, 1993;Fairbairn et al, 2000;Liu et al, 1994;Liu et al, 1999;Reese et al, 2001). Additionally, there have been no signs of hematopoietic clonal expansion in a canine large animal model in which animals transplanted animals MGMT P140K -transduced cells received alkylator therapy over a prolonged time period that also included some escalation in alkylator dose.…”
Section: Genotoxicity Concerns For In-vivo Selection Retroviral-vectmentioning
confidence: 99%